'We don't like the rules and still we keep seeking new ones': The vicious circle of quality control in professional organizations. Issue 1 (7th December 2018) - Wadmann, Sarah; Holm-Petersen, Christina; Levay, Charlotta
Abstract: Standardization, auditing, and performance measurement increasingly characterize the governance of professional organizations. In hospital services, this is expressed in a multiplication of quality assurance programmes, which may be characterized as technologies of quality control. Organizational research shows that the impact of such technologies is profound and often problematic. Even if rooted in professional expertise, they tend to evoke resistance and evasion among professionals. Drawing on Crozier's classic analysis of bureaucratic malfunctions and recent theory of professional hybridity and co-optation, this article brings forth a new aspect of professionals' encounter with managerial forms of governance, as manifested in a case study from the Danish hospital services. Despite scepticism, professional groups with differing status and interests can reinforce a burdensome system of governance with even more standards and intensified measuring, as they seek to use the technologies of quality control to manage uncertainties and enhance their standing in relation to other groups. Hence, professionals can find themselves caught in what we call a vicious circle of quality control. This dynamic, we propose, is essentially of a professional nature; it is through their very efforts to promote their distinctive aspirations that professionals may end up fuelling excessive measurement and detailed controls, thereby making their own work more difficult.